Pengaruh Good Corporate Governance, Corporate Social Responsibility dan Asset Growth terhadap Nilai Perusahaan - Hala, Yusriadi; ., Muh. Akob; ., Asbi Amin (Al-Buhuts, 2024)
This research aims to analyze the influence of Good Corporate Governance, corporate social responsibility and Asset Growth on company value. Data collection uses secondary data. The population is 71 companies in the basic industrial and chemical sectors listed on the Indonesian stock exchange for the 2020-2022 period, while the sample taken using purposive sampling was 11 companies for a period of 3 years which resulted in 33 research samples. The results of this research have been tested for classical assumptions in the form of normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, hypothesis test. The data analysis method uses multiple linear regression techniques. Data were analyzed using the SPSS version 22 program. The results of this research show that Good Corporate Governance and Corporate Social Responsibility have a negative effect on company value, whereas Asset Growth has a positive effect on company value.